Certified Analysis of Economic Industries: Challenges and Opportunities in the Globalization Era - Billy Eka Wardana (Journal of Economics and Regional Science, 2023)
This journal aims to analyze the role of certification in the context of the industrial economy in the era of globalization, with a focus on the challenges and opportunities faced. Certification plays an important role in ensuring the quality of economic industry products and services, as well as increasing trust and compliance with international standards. We also analyze various indicators that are used as a reference in the certification process, such as quality standards, sustainability, and application of the latest technology. The research method used in this journal is descriptive and qualitative analysis. We conducted case studies on several economic industries that have implemented certification, and analyzed their impact on improving the quality, trust and competitiveness of these industries. The results of the research show that certification can be an effective means of dealing with the challenges faced by the economic industry in the globalization era, as well as providing opportunities to access a wider global market. In conclusion, economic industry certification is an effective strategy in overcoming challenges and taking advantage of opportunities in the era of globalization